Existence of Authority Nusantara Capital City in Perspective of Local Government Law - Caesar, Rhendy Harnaloustamy (Constitutionale, 2024)
Establishing the Nusantara Capital City Authority (IKN) through Law No. 3 of 2022 is incompatible with the 1945 Constitution, which only recognizes provinces, regencies, and cities as forms of regional government. The presence of the IKN Authority without the DPRD also raises concerns regarding the supervision and participation of the local community. This article is crafted using a normative legal research method with descriptive analysis. The normative approach is a method to discover and determine what the law should be (ought to be) through analysis of various provisions of legislation by incorporating theories from scientific literature. The statutory approach is employed in this paper, to analyze the existence of the IKN Authority based on a review of laws and regulations pertaining to the law of Regional Government. Data collection in this article involves identifying and cataloging legal materials, researching library materials (writings and scientific works), and other relevant legal sources related to the legal issues discussed in this paper. His appointment by the President also introduces uncertainty in the context of Regional Autonomy as it does not undergo a democratic process. Despite being equivalent to a Minister, the Head of the Authority is still viewed as a local-level administrative official, leading to attributive legal outcomes. Further analysis is required concerning the authority in the legal establishment of the Authority Institution.Although equivalent to a Minister, the Head of the Authority is still considered a local level administrative official, resulting in attributive legal products. Further analysis is needed regarding the authority in the legal formation of the Authority Institution.